DEVELOPING LISTENING SKILLS FOR ACADEMIC PURPOSES - Teshaboyeva Nafisa Zubaydulla qizi; Normamatova Farangiz Tohir qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Effective listening skills are essential for academic success, enabling students to comprehend lectures, participate in discussions, and retain critical information. This article explores the importance of academic listening and identifies common challenges, such as understanding technical terminology, managing diverse accents, and maintaining focus. Strategies for improvement include active listening, vocabulary building, note-taking, exposure to varied speaking styles, and leveraging technology. Practical exercises like dictation, summarizing, and shadowing are recommended, along with tips for sustaining concentration during extended sessions. By implementing these techniques, students can enhance their listening abilities, leading to better academic performance and long-term benefits in learning and communication.